Onshore Thermokarst Primes Subsea Permafrost Degradation. Issue 20 (14th October 2021) - Angelopoulos, Michael; Overduin, Pier P.; Jenrich, Maren; Nitze, Ingmar; Günther, Frank; Strauss, Jens; Westermann, Sebastian; Schirrmeister, Lutz; Kholodov, Alexander; Krautblatter, Michael; Grigoriev, Mikhail N.; Grosse, Guido
Abstract: The response of permafrost to marine submergence can vary between ice‐rich late Pleistocene deposits and the thermokarst basins that thawed out during the Holocene. We hypothesize that inundated Alases offshore thaw faster than submerged Yedoma. To test this hypothesis, we estimated depths to the top of ice‐bearing permafrost offshore of the Bykovsky Peninsula in northeastern Siberia using electrical resistivity surveys. The surveys traversed submerged lagoon deposits, drained and refrozen Alas deposits, and undisturbed Yedoma from the coastline to 373 m offshore. While the permafrost degradation rates of the submerged Yedoma were in the range of similar sites, the submerged Alas permafrost degradation rates were up to 170 % faster. Remote sensing analyses suggest that 54 % of lagoons wider than 500 m along northeast Siberian and northwest American coasts originated in thermokarst basins. Given the abundance of thermokarst basins and lakes along parts of the Arctic coastline, their effect on subsea permafrost degradation must be similarly prevalent. Plain Language Summary: Permafrost is defined as any ground or rock colder than 0 ° C for two or more consecutive years. In unglaciated regions of Siberia during the last ice age, the ground froze 1 km deep. When the ice sheets and glaciers melted at the end of the last Ice Age, millions of square kilometers of this cold permafrost were inundated with seawater on shallow Arctic shelves, creating subsea permafrost. Even today, new permafrost is submerged because of coastal erosion. Once submerged, heat and salt flow thaw the permafrost. However, the rate of subsea permafrost thaw partially depends on its temperature, ice content, and sediment type. Some permafrost areas called Alases already experienced deep thaw and refreezing from Arctic lake formation and drainage. On the southern coastline of the Bykovsky Peninsula in Siberia, we carried out non‐invasive marine geophysical surveys parallel to the coastline to estimate how fast permafrost thaws beneath a submerged Alas next to a lagoon and permafrost areas without Alases. We discovered that subsea permafrost degradation was up to 170 % faster beneath the submerged Alas nearshore. To highlight the broader relevance of these Alas‐lagoon landscapes along the Arctic coastline, we map out Arctic lagoons. Key Points: Subsea permafrost degradation was up to 170% faster below submerged thermokarst basins compared to submerged Yedoma remnants nearshore Re‐worked permafrost beneath thermokarst basins adjacent to lagoons induces rapid offshore thaw Along the assessed Arctic coastline, 54% of lagoons originated in thermokarst basins